Spontaneous abortions among women working in the pharmaceutical industry. Issue 3 (March 1986) - Taskinen, H; Lindbohm, M L; Hemminki, K
Abstract : A register based study was conducted on the pregnancy outcome of female workers in eight Finnish pharmaceutical factories to determine whether they had a higher risk of spontaneous abortion than the general population or matched controls. Information about all female workers who had been employed in the factories during the years 1973 or 1975 (four factories) to 1980 was obtained from the employers. The workers' pregnancy data were collected from the nation wide hospital discharge register and polyclinic data of hospitals from 1973 to 1981. The total number of 1795 pregnancies included 1179 deliveries, 142 spontaneous abortions, and 474 induced abortions. The spontaneous abortion rate (the number of spontaneous abortions X 100, divided by the number of spontaneous abortions plus the number of births) during employment was 10.9% and before/after employment 10.6%. The rate for all the women in the corresponding central hospital districts was 11.3% [corrected] during the study period. A case-control study was also carried out in which the cases were 44 women who had a spontaneous abortion during employment in the pharmaceutical factory. Three age matched female pharmaceutical factory workers who had given birth to a child were chosen as controls for every case. The information about occupational exposures was collected from questionnaires completed by the occupational physician or nurse at the factory. The response rate was 93%. Exposure to chemicals was more common among the cases than among the controls. For methylene chloride, a solvent commonly used in the pharmaceutical industry, the increase in odds ratio of borderline significance (odds ratio 2.3, p = 0.06). In a logistic regression model (which included oestrogen exposure, solvent exposure frequency of the usage, and heavy lifting) the odds ratio was increased for oestrogens (odds ratio 4.2, p = 0.05) and for continuous heavy lifting (odds ratio 5.7, p = 0.02). The odds ratio for spontaneous abortions was greater among those exposed to four or more solvents (odds ratio 3.5, p=0.05) than among those exposed to one to three solvents (odds ration 0.8, p=0.74).